Influence of intimate partner violence and male involvement on maternal healthcare services utilisation in Nigeria - Adetutu, O. M.; Oyinlola, F. F.; Oyelakin, T. E.; Ofili, F. L. (Frontiers in Global Women's Health, 2024)
Low antenatal care attendance and skilled birth attendance has been documented to be responsible for maternal mortality and morbidity in Nigeria. While available evidence suggests mixed findings on uptake of maternal health care services in the context of abusive spousal relationships, male involvement has been established to promote maternal health. Yet, studies which consider mediating influence of intimate partner violence on male involvement and maternal health care services are sorely missing in Nigeria. We hypothesised that maternal health care uptake in abusive marital unions has implications for male involvement in pregnancy care and this has been largely overlooked in Nigeria. This study extracted data from the 2018 Nigeria Demographic and Health Survey (NDHS). The 2018 NDHS is a nationally representative secondary data. The data used a two-stage stratified and multistage sampling technique to collect information from the respondents. In this study, data were extracted for women who were sexually active and of reproductive age (15-49 years), not pregnant in five years prior the survey (n=7847). The results indicated (77%) (ANC) and (47%) skilled birth attendance. The mediating influence of IPV on male involvement resulted in women who experienced sexual violence more likely to use heath facility for antenatal care (OR=3.20; C.I: 1.20-8.50). Women whose partners were involved in health decision making had lower odds of antenatal care attendance (OR=0.64; C.I: 0.44-0.94). Also, women whose partners were involved in spending their earnings had lower probability of antenatal care attendance (OR=0.72; C. I: 0.55-0.96). Yet, the mediating influence of IPV on male involvement resulted in a lower likelihood of use of skilled delivery for emotionally abused women (OR=0.58; C.I: 0.39-0.85). Women whose partners were involved in spending their earnings had higher odds of using skilled delivery (OR=2.15; C.I: 1.79-2.56). Yet, women whose partners were involved in their health decision-making had lower odds of using skilled delivery (OR=0.46; C. I: 0.34-0.62). This study held the philosophical stance that IPV mediated the influence of male involvement on maternal health care uptake while intimate partner violence had an inconsistent influence on maternal health care uptake. Policy interventions should focus on enhancing socioeconomic status of women.